Effect of vitamin C on turbot (Scophthalmus maximus) using different experimental diets in feeding - Fernández-Pato, Carlos; Martínez-Tapia, Concha; Chereguini-Fernández-Maquieira; María del Olvido; Sola, Esperanza (2012)
The use of vitamin C on turbot has been repported in this paper. Groups of juvenile fish were fed in different diet, oxidated or not food combined whether or not with ascorbic acid. The growth of both groups were compared with oneway variance analysis, that showed no significative differences p>0.05. Also the effect of vitamin C on survival were analysed by actuarial method of Cutler-Ederer and groups compared by statistics of Breslow and Mantel-Cox. Groups feed on ascorbic acid(with oxidated food) showed significative differences with the equivalent without ascorbic acid (p=0.0000). Others groups did not show them (p>0.05). Dans ce papier, on montre l'utilization de la vitamine C par le turbot. Des groupes de poissons jeunes ont été alimentés avec des dietes différentes, oxydées et non oxydées, combinées avec et sans acide ascorbique. La croissance des deux groupes a été comparée avec un analysis de la variance unifactoriel, et n'a pas montré de différences significatives (p>0.05). On a aussi analysé l'effet de la vitamine sur la survie avec le méthode de Cutler-Ederer et les groupes ont été comparés avec le méthode statistique de Brestow et Mantel-Cox. Les groupes alimentés avec l'acide ascorbique (nourriture oxydée) ont montrés des dtfférences significatives avec le groupe sans acide ascorbique (p=0.0000). Des autres groupes ne le montrent pas (p>0.05). No